2021
DOI: 10.1159/000520811
|View full text |Cite
|
Sign up to set email alerts
|

Early Nutrition and Later Excess Adiposity during Childhood: A Narrative Review

Abstract: BACKGROUND: Studies on childhood obesity mainly focus on the genetic component and on the lifestyle that may be associated with the development of obesity. However, the study of perinatal factors in their programming effect towards future obesity in children or adults is somewhat more recent and there are still mechanisms to be disentangled. SUMMARY: In this narrative review, a comprehensive route based on the influence of some early factors in life in the contribution to later obesity development is presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 83 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…There is currently strong evidence concerning the need to design and promote forthcoming efficient strategies and approaches to limit early obesity. This constitutes a strong demand, which may improve lifestyle behaviors such as infant eating behaviors, contributing also to define the potential impact of other mechanisms, such as the impact of perinatal factors including mothers' nutritional habits during gestation, epigenetics, or microbiome [42]. Interestingly, a recent meta-analysis showed that Mediterranean diet-based interventions may exert a considerable impact on lowering the BMI and decreasing obesity in children and adolescents at ages between 3 and 18 years old [43].…”
Section: Discussionmentioning
confidence: 99%
“…There is currently strong evidence concerning the need to design and promote forthcoming efficient strategies and approaches to limit early obesity. This constitutes a strong demand, which may improve lifestyle behaviors such as infant eating behaviors, contributing also to define the potential impact of other mechanisms, such as the impact of perinatal factors including mothers' nutritional habits during gestation, epigenetics, or microbiome [42]. Interestingly, a recent meta-analysis showed that Mediterranean diet-based interventions may exert a considerable impact on lowering the BMI and decreasing obesity in children and adolescents at ages between 3 and 18 years old [43].…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition is a key factor in child development ( 1 ), substantially influencing not only physical but also mental and cognitive health ( 2 ). Moreover, early life nutrition has been found to have long-term effects on health, which include modulating the risk for non-communicable diseases such as obesity, diabetes mellitus, and cardiovascular disease ( 3 , 4 ). At the same time, young children are particularly vulnerable to nutrient deficiencies, as nutrient requirements per kg body weight are high ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different maternal factors (e.g., obesity, gestational weight gain, socioeconomic characteristics) have been identified as influencing infant adiposity ( 1 , 3 ). Lifestyle and nutrition interventions may play a key role in improving maternal metabolic profiles and reducing the risk of obesity in the next generation ( 4 ). Specifically, an optimal diet quality during pregnancy, as well as high adherence to a DASH diet or a Mediterranean dietary pattern has been associated with a better glycemic status and a reduce size and adiposity at birth ( 5 8 ).…”
Section: Introductionmentioning
confidence: 99%